2020
DOI: 10.3390/cancers12102724
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polypharmacy for Chronic Ailments in Colon Cancer Patients: A Review Focused on Drug Repurposing

Abstract: Colorectal cancer is characterized by high incidence worldwide. Despite increased awareness and early diagnosis thanks to screening programmes, mortality remains high, particularly for patients with metastatic involvement. Immune checkpoint inhibitors or poly (ADP-ribose) polymerase (PARP)-inhibitors have met with disappointing results when used in this setting, opposed to other malignancies. New drugs with different mechanisms of action are needed in this disease. Drug repurposing might offer new therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 119 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…A recent review reported that users of SSRIs and other antidepressants did not experience any notable effect on the risk of colon cancer. Moreover, no clear evidence of either beneficial or harmful association was found between antidepressant treatment and cancer, including colon cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review reported that users of SSRIs and other antidepressants did not experience any notable effect on the risk of colon cancer. Moreover, no clear evidence of either beneficial or harmful association was found between antidepressant treatment and cancer, including colon cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, no evidence was found in humans of either a beneficial or a harmful association between antidepressant treatment and cancer, including breast cancer and colon cancer [ 33 , 37 , 38 ]. If, however, the response to SSRIs in humans is indeed similar to that of rodents, then these results indicate that special care has to be taken when prescribing sertraline or citalopram as antidepressants to cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Drug repurposing or repositioning involves using approved drugs for conditions different from their original indication [13][14][15]. Several drugs have acquired additional use in the past years and have been reintroduced into practice fueled by this phenomenon.…”
Section: Repurposing Approved Drugs In Colon Cancermentioning
confidence: 99%
“…Appropriate management through continued use of statins may lead to better results in patients [ 21 ]; however, statin use may have different effects in patients with dyslipidemia and dyslipidemia patients with cancer. In this study, we evaluated the effects of continued use of post-diagnostic statins and the doses of these drugs on mortality in dyslipidemia patients with or without GI cancer.…”
Section: Introductionmentioning
confidence: 99%